2020
DOI: 10.3390/ma13225109
|View full text |Cite
|
Sign up to set email alerts
|

Dental Aerosol as a Hazard Risk for Dental Workers

Abstract: Standard dental procedures, when using a water coolant and rotary instruments, generate aerosols with a significantly higher number of various dangerous pathogens (viruses, bacteria, and fungi). Reducing the amount of aerosols to a minimum is mandatory, especially during the new coronavirus disease, COVID-19. The study aimed to evaluate the amount of aerosol generated during standard dental procedures such as caries removal (using dental bur on a high and low-speed handpiece and Er:YAG laser), ultrasonic scali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(102 citation statements)
references
References 37 publications
(58 reference statements)
4
59
0
2
Order By: Relevance
“… 42–44 It is important to highlight the benefits of utilizing laser-assisted therapy for adult patients as well, due to its advantages in producing less aerosols, eliminating tooth vibration, minimal to less local anesthetic administration and providing analgesic effects. 45 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 42–44 It is important to highlight the benefits of utilizing laser-assisted therapy for adult patients as well, due to its advantages in producing less aerosols, eliminating tooth vibration, minimal to less local anesthetic administration and providing analgesic effects. 45 …”
Section: Resultsmentioning
confidence: 99%
“…[42][43][44] It is important to highlight the benefits of utilizing laser-assisted therapy for adult patients as well, due to its advantages in producing less aerosols, eliminating tooth vibration, minimal to less local anesthetic administration and providing analgesic effects. 45 It is significant to emphasize tooth brushing with fluoridated toothpaste for all patients, including children, to prevent tooth decay. 46 A report by Addy highlighted the importance of oral hygiene by stating that the majority of toothpastes, if not all of them, contain detergents/surfactants with significant antimicrobial properties, which are similar to those in the detergents of many hand-washing formulations recommended against coronavirus.…”
mentioning
confidence: 99%
“…This is especially important as smaller aerosols may carry SARS-CoV-2 virus (0.06 -0.14 µm 25 ). Some investigations have used aerosol sampling techniques 21,[26][27][28][29][30][31] , but suffer from limited sampling of large aerosols and splatters or incorrect use of the sampling devices.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent report, the World Health Organization (WHO) acknowledged the need for dental work to continue and highlighted that this necessitates the use of aerosol-producing tools [8,9]. Also, some other recent studies suggested the use of new suction systems and an Er:YAG laser, as well as the correct application of a disinfectant in order to improve biological safety in the dental clinic/office especially during the COVID-19 pandemic [10,11].…”
Section: Introductionmentioning
confidence: 99%